Economic efficiency of stingless bee farms in Peninsular Malaysia estimated by Data Envelopment Analysis (DEA) - Che Soh, Norhidayah; Samsuddin, Nur Syahirah; Ismail, Mohd Mansor (Universiti Putra Malaysia Press, 2021)
The commercial stingless beekeeping industry has good economic growth potential in Malaysia, which is a tropical country rich in flora that serves as food sources for stingless bees. Local consumption of honey is increasing and its production locally can be raised to meet the demand by sustainable stingless beekeeping. An important indicator that measures the success of the industry is the economic efficiency of the farm. This study hence examined the cost efficiency (CE), technical efficiency (TE), and allocative efficiency (AE) of commercial stingless beekeeping farms in the East Coast and Northern regions of Peninsular Malaysia using Cost Data Envelopment Analysis (DEA) under the assumption of Constant Return to Scale (CRS). Interviews with 47 respondents in the East Coast region and 28 respondents in the Northern region showed that the average CE scores for the two regions were 0.291 and 0.172, respectively. TE for the East Coast region and Northern region were 0.656 and 0.385 while mean AE scores of 0.445 and 0.404 were obtained. Factors that influenced the efficiency of the farms included farmers’ years of schooling and extension officer visits. In conclusion, CE, TE, and AE of commercial stingless bee honey production in Peninsular Malaysia were fairly low, and the determinants responsible for this low efficiency is of concern. Economic efficiency in stingless beekeeping needs to be further elevated to optimise productivity.